Acute orchitis deciphered: Coxsackievirus B strains are the main etiology and their presence in semen is associated with acute inflammation and risk of persistent oligozoospermia - Pilatz, Adrian; Arneth, Borros; Kaiser, Rolf; Heger, Eva; Pirkl, Martin; Böttcher, Sindy; Fritzenwanker, Moritz; Renz, Harald; Mankertz, Annette; Schuppe, Hans-Christian; Wagenlehner, Florian; Justus Liebig University Giessen (My University, 2023)
Although various viruses are considered to be the clinical cause for acute orchitis, it is completely unclear to what extent and which viruses are etiologically involved in acute orchitis and what the clinic and course of these patients are like. Therefore, a prospective study was set up to decipher acute isolated orchitis. Between July 2007 and February 2023, a total of 26 patients with isolated orchitis were recruited and compared with 530 patients with acute epididymitis. We were able to show for isolated orchitis, that (1) orchitis is usually of viral origin (20/26, 77%) and enteroviruses with coxsackievirus B strains (16/26, 62%) are predominant, (2) virus isolates could be received from semen indicating the presence of replication-competent virus particles, (3) a polymerase chain reaction (PCR) for enteroviruses should be conducted using semen provided at the onset of disease, because the virus is not detectable in serum/urine, (4) there is a circannual occurrence with the maximum in summer, (5) orchitis is associated with a characteristic inflammatory cytokine panel in the semen and systemic inflammation, (6) orchitis is usually rapidly self-limiting, and (7) about 30% of patients (6/20) suffer ongoing oligozoospermia. These seven emerging aspects are likely to fundamentally change thinking and clinical practice regarding acute isolated orchitis.
Keywords: coxsackievirus; enterovirus; epididymitis; fertility; mumps; Orchitis; ddc:610